Urban gig workers in Indonesia during COVID-19: The experience of online 'ojek' drivers. (1st January 2021) - Rachmawati, Riani; Safitri,; Zakia, Luthfianti; Lupita, Ayu; De Ruyter, Alex
Abstract : This paper uses case study evidence to examine how COVID-19 has impacted on the working conditions of urban gig workers (online 'ojek' riders). Initial findings suggest that the platform companies use the term 'partner' to commandeer low-cost labour and thereby avoid the obligations required of a contract of employment, and that this vulnerability has become more evident in COVID-19 pandemic conditions. The findings suggest that the platform companies should pay more attention to worker feedback to create a better working environment, as decent work will better be achieved with responsible corporate governance, good management, and strong worker-management relationships.